2016
DOI: 10.1038/srep19737
|View full text |Cite
|
Sign up to set email alerts
|

Hemispheric Asymmetry of Endogenous Neural Oscillations in Young Children: Implications for Hearing Speech In Noise

Abstract: Speech signals contain information in hierarchical time scales, ranging from short-duration (e.g., phonemes) to long-duration cues (e.g., syllables, prosody). A theoretical framework to understand how the brain processes this hierarchy suggests that hemispheric lateralization enables specialized tracking of acoustic cues at different time scales, with the left and right hemispheres sampling at short (25 ms; 40 Hz) and long (200 ms; 5 Hz) periods, respectively. In adults, both speech-evoked and endogenous corti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
20
0
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 26 publications
4
20
0
4
Order By: Relevance
“…The presence of a distinct Tb response to the 25 ms ISI tonepairs, in particular, suggests that there are neuronal ensembles in the left hemisphere capable of responding to stimuli presented as quickly as 25 ms. These results provide evidence of left hemisphere specialisation for rapid temporal processing in children aged 7 and 9 years, and are consistent with previous findings of Thompson et al (2016) who observed leftward lateralisation of high-frequency (20-50Hz) endogenous cortical oscillations at the younger ages of 3-5 years.…”
Section: Hemispheric Asymmetries In the Tb Responsesupporting
confidence: 92%
See 3 more Smart Citations
“…The presence of a distinct Tb response to the 25 ms ISI tonepairs, in particular, suggests that there are neuronal ensembles in the left hemisphere capable of responding to stimuli presented as quickly as 25 ms. These results provide evidence of left hemisphere specialisation for rapid temporal processing in children aged 7 and 9 years, and are consistent with previous findings of Thompson et al (2016) who observed leftward lateralisation of high-frequency (20-50Hz) endogenous cortical oscillations at the younger ages of 3-5 years.…”
Section: Hemispheric Asymmetries In the Tb Responsesupporting
confidence: 92%
“…Nevertheless, our results clearly demonstrate that hemispheric preferences for fast and slow modulations are present in children at age 7 and 9. In the context of previous findings byThompson et al (2016) and Vanvooren et al (2014), our results suggest that temporal processing asymmetries may become more consistent from at least 7 years. Earlier inconsistencies across studies of younger children may reflect reduced prominence of functional asymmetries, and therefore, difficulty identifying such asymmetries consistently.…”
supporting
confidence: 84%
See 2 more Smart Citations
“…Additionally, gamma activity may reflect the extent to which processing in distinct brain regions are coordinated Engel, König, Kreiter, & Singer, 1991). The areas that support language and reading are distributed throughout the brain; therefore an age-related decrease in gamma power, as observed from scalp electrodes, could also reflect greater localization, specialization, and efficiency of cortical processing with maturation (Benasich et al, 2008;Thompson et al, 2016;Tierney et al, 2014).…”
Section: Discussionmentioning
confidence: 99%